Evaluate the limit m → ∞ lim n = 1 ∏ m e 1 / ( 2 n ) n = 1 ∏ m e 1 / ( 2 n − 1 )
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
n = 1 ∏ ∞ e ( 2 n − 1 ) 1 = e ∑ n = 1 ∞ ( 2 n − 1 ) 1 = α n = 1 ∏ ∞ e 2 n 1 = e ∑ n = 1 ∞ 2 n 1 = β So β α = e ∑ n = 1 ∞ ( 2 n − 1 ) 1 − 2 n 1 = e lo g ( 2 ) = 2
Note
n = 1 ∑ ∞ 2 n − 1 1 − 2 n 1 = 1 − 2 1 + 3 1 − . . = lo g ( 2 )
Problem Loading...
Note Loading...
Set Loading...
By expanding prior to taking the limit, we find:
exp(1/1 + 1/3 + 1/5 + ... + 1/(2*m-1)) / exp(1/2 + 1/4 + ... + 1/2m) =
exp(1 - 1/2 + 1/3 - 1/4 + .... - 1/2m).
As m-> infinity, the quantity in parenthesis is well known to approach ln(2) (Google "sum of alternating harmonic series for an explanation"). Therefore, the limit is:
exp(ln(2)) = 2